Flexible flame-retardant polyolefin insulating material for high-flexibility drag chain cable as well as preparation method and application of flexible flame-retardant polyolefin insulating material
By using the use of phosphorus -containing flame retardant surfaces to modify boron nitride and polyphothexide nano -nano wires such as the surface of phosphorus -containing flame retardant surfaces in high flexible drag chain cable materials, it is difficult to take into account the combustible flame retardant and flexible performance. The problem realizes the comprehensive performance of materials.
Patent Information
- Application Number
- CN202411945605.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-24
AI Technical Summary
The existing high-flexible drag chain cable insulation materials are difficult to balance between flame retardant and flexible properties. The addition of traditional flame retardant will lead to a decrease in the toughness and ductility of the material.
The phosphorus -containing flame -retardant surface modifiers and boron nitride and polyphothexylhumin are modified to modify the components of magnesium hydroxide nano wiring. The coordinated design such as the sirrilla amine coupling KH550 is used to improve the flame retardability, flexibility and insulation performance of the material.
It significantly improves the flame retardancy, flexibility and insulation properties of highly flexible drag chain cable materials, solves the problem of difficulty in balancing the flame retardancy and flexibility of traditional materials, extends the service life of the material and reduces maintenance costs.
Smart Images

Figure CN119350741A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of cable materials, and in particular to a flexible flame-retardant polyolefin insulation material for a highly flexible drag chain cable, and a preparation method and application thereof. Background Art
[0002] With the rapid development of industrial automation, the demand for dynamic high-flexibility drag chain cables in the fields of robotics, machine tool manufacturing, logistics and transportation systems is growing. These cables need to withstand frequent bending, stretching and twisting under complex working conditions, and are exposed to high temperature, humidity, mechanical wear and electrical environment for a long time, which puts extremely high demands on the performance of cable materials. As the insulation material at the core of the cable, it not only needs to have excellent flexibility to adapt to high-frequency dynamic bending and complex motion trajectories, but also needs to have excellent flame retardancy to ensure that it is not easy to burn in a fire or high temperature environment and reduce the release of smoke and toxic gases, thereby ensuring equipment safety and human health. In addition, weather resistance, oxidation resistance and processing stability are also key factors to meet the needs of long-term use without aging, cracking or performance degradation. Therefore, polyolefin insulation materials with dual excellent properties of flexibility and flame retardancy have become the core research topic in this field. Its development can not only significantly improve the service life and reliability of drag chain cables, but also broaden their application range in harsh industrial environments, which is of great significance to promoting technological progress in related industries.
[0003] At present, in the research on insulation materials for highly flexible drag chain cables, the balance between flexibility and flame retardancy is still a key issue to be solved. For example, the Chinese patent with publication number CN115322573A discloses a 125°C halogen-free and non-toxic super B1 flame-retardant polyolefin material, which often simply adds flame retardants to the components. However, in practical applications, it has good flexibility but is difficult to take into account high-efficiency flame retardancy. The main reason is that the addition of traditional flame retardants usually leads to a significant decrease in the toughness and ductility of the material. On the other hand, the Chinese patent with publication number CN201663007U discloses a flexible silane cross-linked polyolefin elastomer insulation core, the insulation layer is made of silane cross-linked polyolefin elastic material, but no flame retardant design is adopted, so it cannot meet the flame retardancy requirements. In addition, the existing flame retardant system mostly relies on inorganic fillers or halogen flame retardants. The former is difficult to be compatible with flexibility requirements, and the latter is strictly restricted due to smoke and toxicity problems. Therefore, there is an urgent need for a material design and optimization solution that can achieve efficient synergy between flexibility and flame retardancy, so as to break through the existing technical bottleneck and meet the actual application needs of highly flexible drag chain cables. Summary of the invention
[0004] (1) Technical issues solved The purpose of the present invention is to provide a flexible flame-retardant polyolefin insulation material for a highly flexible drag chain cable, so as to solve the problem that the current insulation material has insufficient flame retardancy and flexibility.
[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: Flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables, comprising the following components by weight: 5-15 parts of phosphorus-containing flame retardant surface-modified boron nitride, 3.0-10.0 parts of polyphosphazene-modified magnesium hydroxide nanowires, 0.3-0.8 parts of silane coupling agent KH550, 50-80 parts of polyolefin matrix resin, 3.0-8.0 parts of polyethylene grafted maleic anhydride, 0.1-0.5 parts of antioxidant 1010, 0.2-0.5 parts of ultraviolet absorber 531, 2.0-5.0 parts of epoxidized soybean oil, and 0.1-0.3 parts of zinc stearate; The phosphorus-containing flame retardant surface-modified boron nitride is obtained by surface-modifying hydroxyl-modified hexagonal boron nitride with 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and vinyltrimethoxysilane; The hydroxyl-modified hexagonal boron nitride is prepared by an alkaline hydrothermal method. The morphology of the hexagonal boron nitride is a nano-sheet morphology; The polyphosphazene-modified magnesium hydroxide nanowires are prepared by first modifying the magnesium hydroxide nanowires with amino functionalities using a silane coupling agent KH-550, and then further cross-linking and polymerizing hexachlorocyclotriphosphazene and 4,4'-diaminodiphenyl ether to obtain the polyphosphazene-modified magnesium hydroxide nanowires.
[0006] Further, the preparation method of the phosphorus-containing flame retardant surface-modified boron nitride is as follows: by weight, 10 to 20 parts of hydroxyl-modified hexagonal boron nitride, 30 to 40 parts of methanol, 2.0 to 5.0 parts of 60 wt.% sulfuric acid and 20 to 40 parts of deionized water are added to a beaker, stirred at 200 to 300 rpm for 15 to 30 minutes at room temperature to obtain a solution A, which is then transferred to a constant pressure dropping funnel, and 10.0 to 15.0 parts of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxo- The product and 5.0-7.5 parts of vinyltrimethoxysilane are evenly mixed, placed in a three-necked round-bottom culture bottle, heated to 70-80°C, and then solution A is dripped into the three-necked round-bottom culture bottle drop by drop. After the addition is completed, the reaction is carried out at 70-80°C for 8-12 hours. After the reaction is completed, it is cooled to room temperature, and then the solution is filtered and the precipitate is retained. The precipitate is then washed with methanol for 3 times, and finally the precipitate is dried in a vacuum drying oven at 60-80°C for 20-25 hours to obtain the phosphorus-containing flame retardant surface-modified boron nitride.
[0007] Furthermore, the preparation method of the hydroxyl-modified hexagonal boron nitride is as follows: in parts by weight, 10.0-15.0 parts of hexagonal boron nitride and 150-200 parts of 5 mol / L sodium hydroxide are mixed evenly and reacted at 80-90° C. for 240-360 min. After the reaction is completed, the mixture is cooled to room temperature, and then the solution is filtered and the precipitate is retained. The precipitate is then washed with deionized water for 3 times, and finally the precipitate is dried in a vacuum drying oven at 50-70° C. for 10-15 h to obtain hydroxyl-modified hexagonal boron nitride.
[0008] Furthermore, the preparation method of hexagonal boron nitride is as follows: by weight, 20 to 30 parts of a mixture of hexagonal boron nitride powder and zirconium oxide ball milling medium are added to a ball mill according to a mass ratio of 1: (5 to 20), deionized water is added as a dispersion medium, and the solid-liquid mass ratio is controlled to be 1: (4 to 10); 0.1 to 1.0 parts of sodium dodecylbenzene sulfonate dispersant are added to the ball mill, and ball milling is performed in a sealed state, the ball milling speed is controlled at 200 to 500 rpm, and the ball milling time is 10 to 48 h; after the ball milling is completed, the solid material of the ball milled product is separated by centrifugation, and then the solid material is washed 3 to 5 times with deionized water; then the washed solid material is dried in a vacuum drying oven at 50 to 80° C. to constant weight, and finally hexagonal boron nitride is obtained.
[0009] Furthermore, the average diameter of the hexagonal boron nitride is 600-2000 nm, and the average thickness is 10-25 nm.
[0010] The present invention adopts the design of phosphorus-containing flame retardant surface modified boron nitride mainly for enhancing the flame retardancy, flexibility and insulation performance of high-flexible drag chain cable materials. By surface-modifying hydroxyl-modified hexagonal boron nitride with 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and vinyltrimethoxysilane, on the one hand, excellent flame retardancy is given to hexagonal boron nitride, and on the other hand, its dispersibility and interface compatibility in the polyolefin matrix are improved by silane modification, thereby effectively improving the insulation performance of the material while maintaining flexibility. The preparation of hydroxyl-modified hexagonal boron nitride adopts alkaline hydrothermal method to ensure that hexagonal boron nitride has nano-sheet structure and uniform surface functionalization characteristics, which provides a good foundation for subsequent modification. In addition, the phosphorus element in 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide enhances the flame retardant efficiency of the material through synergistic effect, and vinyltrimethoxysilane further improves the insulation performance of the material by improving interface bonding force and uniform dispersion. The synergistic design of each component enables the modified hexagonal boron nitride to maintain the flexibility of the material while improving its flame retardancy and insulation, thereby meeting the multiple performance requirements of highly flexible drag chain cables under complex working conditions.
[0011] Further, the preparation method of the polyphosphazene modified magnesium hydroxide nanowires is as follows: by weight, 40 to 60 parts of magnesium hydroxide nanowires and 200 to 250 parts of anhydrous ethanol are stirred at room temperature for 20 to 30 minutes, and then 2.0 to 4.0 parts of silane coupling agent KH-550 and 5.0 to 10 parts of deionized water are added, and the stirring is continued for 60 to 90 minutes. After the stirring is completed, the precipitate is retained after filtering, and then the precipitate is washed with deionized water for 3 times, and finally, the amino-functionalized magnesium hydroxide nanowires are obtained after vacuum drying at room temperature, and then the amino-functionalized modified hydroxide nanowires are added. Magnesium hydroxide nanowires were dissolved in 180-200 parts of acetonitrile, and then 8.0-12.0 parts of 4,4'-diaminodiphenyl ether and 20-25 parts of triethylamine were added and ultrasonically treated for 25-35 minutes to obtain an amino-functionalized magnesium hydroxide nanowire mixed solution. Then, 50-60 parts of a mixed solution of hexachlorocyclotriphosphazene and acetonitrile were added dropwise thereto, wherein the mass ratio of hexachlorocyclotriphosphazene to acetonitrile was 1:25. After the addition was completed, the reaction was stirred at 40-45 minutes for 180-240 minutes. After the reaction was completed, the solution was filtered and the precipitate was retained and washed with acetonitrile and deionized water for 3 times respectively. Then, the washed precipitate was dried in a vacuum drying oven at 40-50°C to constant weight, and finally polyphosphazene-modified magnesium hydroxide nanowires were obtained.
[0012] Furthermore, the preparation method of the magnesium hydroxide nanowires is as follows: 0.4-0.6 mol of magnesium nitrate hexahydrate and 5 mol of 50 wt.% sodium hydroxide solution are ultrasonically treated for 20-30 minutes to obtain a uniform solution, 2 mol of anhydrous ethanol is added and stirred for 5 minutes, and then the solution is added to a Teflon-lined autoclave, heated to 180-220° C. and kept warm for 5-10 hours, and after cooling to room temperature, the solution is filtered and the precipitate is retained, followed by washing with deionized water for 6 times, and finally dried in a vacuum drying oven at 60-80° C. to constant weight to obtain magnesium hydroxide nanowires.
[0013] The present invention adopts the design of polyphosphazene modified magnesium hydroxide nanowires mainly to enhance the flame retardancy and flexibility of high-flexibility drag chain cable materials. The magnesium hydroxide nanowires are amino-functionalized by silane coupling agent KH-550 to improve its surface activity and interfacial compatibility with the polyolefin matrix; then hexachlorocyclotriphosphazene and 4,4'-diaminodiphenyl ether are cross-linked and polymerized to form a polyphosphazene structure layer on the surface of the magnesium hydroxide nanowires, which not only significantly enhances the flame retardancy of the nanowires, but also improves its dispersion stability and the reinforcing effect on the matrix. Magnesium hydroxide nanowires are prepared by a hydrothermal method to ensure that they have a high degree of crystallinity and a nanowire-like structure, providing excellent basic performance for subsequent modifications; the introduction of polyphosphazene further improves the thermal stability and flame retardant efficiency of the material through synergistic effects, while maintaining the flexibility and processing performance of the polyolefin matrix. The synergy of the design of each component enables the material to significantly improve flexibility while meeting the high flame retardancy requirements, thereby adapting to the complex working conditions and long life requirements of dynamic high-flexibility drag chain cables.
[0014] The present invention adopts the coordinated design of silane coupling agent KH550, polyolefin matrix resin, polyethylene grafted maleic anhydride and multiple additives, which is mainly used to enhance the flexibility, processing performance and aging resistance of flexible flame-retardant polyolefin insulation materials. Silane coupling agent KH550 significantly improves the uniformity and mechanical stability of the material by improving the interfacial bonding force between the filler and the polyolefin matrix; polyethylene grafted maleic anhydride further enhances the compatibility and flexibility of the matrix, ensuring the reliability of the material under dynamic bending and complex stress conditions. Antioxidant 1010 and ultraviolet absorber 531 work synergistically to effectively improve the material's antioxidant and ultraviolet aging resistance, thereby extending the material's service life in harsh environments. Epoxidized soybean oil, as a plasticizer, gives the material better flexibility and processing fluidity, while zinc stearate improves the material's processing stability and dispersibility through lubrication. The organic combination of these components enables the material to have good aging resistance and processing performance while maintaining excellent flexibility, meeting the multiple performance requirements of high-flexibility drag chain cables.
[0015] The present invention also provides a method for preparing a flexible flame-retardant polyolefin insulation material for a highly flexible drag chain cable, comprising the following steps: S1. Premixing of raw materials: according to the ratio, add the phosphorus-containing flame retardant surface-modified boron nitride, polyphosphazene-modified magnesium hydroxide nanowires and silane coupling agent KH550 into a high-speed mixer for stirring, control the speed to 1200-2000 r / min, stir at high speed for 30-45 minutes to mix evenly, then continue to add the remaining components, continue stirring at the same speed for 25-35 minutes to obtain a premix.
[0016] S2. Melt blending: The premix of S1 is put into a twin-screw extruder for melt blending. The temperatures of the various temperature zones of the extruder are set in sequence: zone 1 120~150℃, zone 2 160~190℃, zone 3 190~220℃, and the die head temperature is 200~230℃. During the blending process, the screw speed is controlled at 200~300 r / min, and the melting time is controlled at 3~7 min.
[0017] S3. Cooling and granulation: After the molten material extruded in step S2 is extruded through an extruder head, the material cooled to room temperature is sent to a pelletizer through a conveying device and cut into uniform particles to obtain a flexible flame-retardant polyolefin insulation material masterbatch.
[0018] S4. Extrusion molding: The masterbatch prepared in step S3 is used for extrusion molding of the insulation layer through a single screw extruder. The barrel temperature of the extruder is set to: 160~180℃ for zone 1, 180~200℃ for zone 2, 200~220℃ for zone 3, the head temperature is 220~250℃, and the screw speed is controlled at 50~120 r / min. Finally, a flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables is obtained.
[0019] The present invention also provides a flexible flame-retardant polyolefin insulation material for a highly flexible drag chain cable, and its application in a dynamic highly flexible cable in the fields of industrial automation equipment, robots, machine tool manufacturing, and logistics transportation systems.
[0020] The present invention adopts the coordinated design of phosphorus-containing flame retardant surface-modified boron nitride, polyphosphazene-modified magnesium hydroxide nanowires and polyolefin matrix, which is mainly used to enhance the flexibility, flame retardancy and processing performance of high-flexibility drag chain cable materials. By premixing the modified hexagonal boron nitride and polyphosphazene-modified magnesium hydroxide nanowires with the silane coupling agent KH550, the dispersibility and interfacial compatibility of the filler and the polyolefin matrix are significantly improved; then in the melt blending stage, by precisely controlling the temperature zone, rotation speed and melting time, the materials are ensured to be uniformly mixed and form a stable structure, thereby giving the material excellent flexibility and flame retardancy. The cooling granulation process ensures the processing stability and operability of the material, while the extrusion molding process optimizes the insulation performance and molding quality of the material. The synergistic design of each component and process step not only meets the flexibility requirements of the dynamic high-flexibility drag chain cable in complex mechanical movements, but also takes into account the flame retardancy, insulation and processing performance, so that the material has a wide range of application prospects in industrial automation equipment, robots, machine tool manufacturing and logistics transportation systems.
[0021] (3) Beneficial technical effects 1. The present invention effectively overcomes the technical bottleneck of the difficulty in balancing flame retardancy and flexibility in the prior art through the innovative design of surface-modified boron nitride with phosphorus-containing flame retardants, and significantly improves the flame retardancy, flexibility and insulation performance of high-flexibility drag chain cable materials. The synergistic flame retardant effect of hydroxyl-modified hexagonal boron nitride combined with 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide ensures the safety of the material in a dynamic bending environment; the surface modification of vinyltrimethoxysilane not only improves the compatibility of the filler with the polyolefin matrix, but also improves the insulation performance and processability. The components work synergistically through reasonable proportions and optimized processes to achieve a comprehensive improvement in performance, giving the material a longer service life and higher reliability. The invention has broad application prospects in the fields of industrial automation equipment, robots and logistics transportation, and provides a high-performance, stable and environmentally friendly solution for industry development.
[0022] 2. The present invention significantly improves the flame retardancy and flexibility of high-flexibility drag chain cable materials through the design of polyphosphazene-modified magnesium hydroxide nanowires, overcoming the pain point of the difficulty in balancing flame retardancy and flexibility in the prior art. Polyphosphazene synergizes with magnesium hydroxide nanowires modified with silane coupling agents to enhance the dispersibility and interfacial bonding strength of nanowires in the polyolefin matrix, achieving a balanced improvement in flame retardant efficiency and material toughness. At the same time, the high-crystallinity nanowires prepared by the hydrothermal method ensure excellent mechanical reinforcement, and the polyphosphazene structural layer further improves thermal stability and flame retardant properties. Compared with traditional flame retardant materials, the present invention exhibits better flame retardancy, flexibility and processing stability under dynamic high-flexibility conditions, prolongs the service life of cables, reduces maintenance costs, and promotes the application and development of flexible flame retardant materials in the field of high-end cables.
[0023] 3. The present invention significantly improves the flexibility, processing performance and aging resistance of flexible flame-retardant polyolefin insulation materials through the coordinated design of components such as silane coupling agent KH550, polyethylene grafted maleic anhydride, and antioxidant 1010, and achieves a balance between flexibility and flame retardancy compared to the prior art. Silane coupling agent improves the interfacial bonding between filler and matrix, polyethylene grafted maleic anhydride enhances matrix compatibility, epoxidized soybean oil and zinc stearate respectively impart excellent flexibility and processing stability, and antioxidants and ultraviolet absorbers synergistically improve the material's antioxidant and ultraviolet resistance. This design effectively solves the problem of fast aging and easy cracking of flexible drag chain cables under dynamic stress conditions, significantly prolongs product service life, reduces maintenance costs, and plays an important role in promoting the development of the high-end cable industry.
[0024] 4. The present invention significantly improves the flexibility, flame retardancy and processing performance of high-flexibility drag chain cable materials through the coordinated design of boron nitride modified by phosphorus-containing flame retardant surface, polyphosphazene modified magnesium hydroxide nanowires and polyolefin matrix, overcoming the bottleneck of the difficulty in balancing flexibility and flame retardancy in the prior art. The modified boron nitride and polyphosphazene modified magnesium hydroxide nanowires work synergistically to improve the filler dispersion and interfacial bonding strength. The melt blending and extrusion molding process optimizes the uniformity and insulation properties of the material. The precise coordination of each component and process ensures the flexibility and long life of the material in dynamic mechanical movement. Compared with traditional materials, the present invention exhibits more excellent flame retardant properties and mechanical durability in the fields of robots, machine tools and logistics transportation. At the same time, it has processing stability and broad application prospects, which plays an important role in promoting the development of the industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the infrared Fourier spectrum of the hexagonal boron nitride prepared in Example 1 of the present invention.
[0026] Figure 2 This is the infrared Fourier spectrum of the surface-modified hexagonal boron nitride with phosphorus-containing flame retardant prepared in Example 1 of the present invention.
[0027] Figure 3 This is a scanning electron microscope morphology image of the surface modified hexagonal boron nitride with phosphorus-containing flame retardant prepared in Example 1 of the present invention.
[0028] Figure 4 This is the infrared Fourier spectrum of the magnesium hydroxide nanowires prepared in Example 1 of the present invention.
[0029] Figure 5 This is the infrared Fourier spectrum of the phosphazene-modified magnesium hydroxide nanowires prepared in Example 1 of the present invention.
[0030] Figure 6 This is a morphology diagram of the magnesium hydroxide nanowires prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0032] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0033] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies Example 1 The flexible flame-retardant polyolefin insulation material for high-flexible drag chain cables comprises the following components by weight: 5 parts of phosphorus-containing flame retardant surface-modified boron nitride, 3.0 parts of polyphosphazene-modified magnesium hydroxide nanowires, 0.3 parts of silane coupling agent KH550, 50 parts of polyolefin matrix resin, 3.0 parts of polyethylene grafted maleic anhydride, 0.1 parts of antioxidant 1010, 0.2 parts of ultraviolet absorber 531, 2.0 parts of epoxidized soybean oil, and 0.1 parts of zinc stearate; The preparation method of the phosphorus-containing flame retardant surface-modified boron nitride of this embodiment is as follows: in parts by weight, 10 parts of hydroxyl-modified hexagonal boron nitride, 30 parts of methanol, 2.0 parts of 60wt.% sulfuric acid and 20 parts of deionized water are added to a beaker, stirred at 200rpm for 15min at room temperature to obtain a solution A, which is then transferred to a constant pressure dropping funnel, and 10.0 parts of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 5.0 parts of vinyltrimethoxysilane are mixed evenly, placed in a three-mouth round-bottom culture bottle, heated to 70°C, and then the A solution is dripped into the three-mouth round-bottom culture bottle drop by drop, reacted at 70°C for 8h after the dropwise addition, cooled to room temperature after the reaction is completed, and then the solution is filtered and the precipitate is retained, and then the precipitate is washed with methanol 3 times, and finally the precipitate is dried in a vacuum drying oven at 60°C for 20h to obtain a phosphorus-containing flame retardant surface-modified boron nitride. The preparation method of hydroxyl-modified hexagonal boron nitride is as follows: by weight, 10.0 parts of hexagonal boron nitride and 150 parts of 5 mol / L sodium hydroxide are mixed evenly and reacted at 80°C for 240 minutes. After the reaction is completed, it is cooled to room temperature, and then the solution is filtered and the precipitate is retained. Then, the precipitate is washed with deionized water for 3 times, and finally the precipitate is dried in a vacuum drying oven at 50°C for 10 hours to obtain hydroxyl-modified hexagonal boron nitride. The preparation method of hexagonal boron nitride is as follows: by weight, 20 parts of a mixture of hexagonal boron nitride powder and zirconium oxide ball milling medium are added to a ball mill at a mass ratio of 1:5, deionized water is added as a dispersion medium, and the solid-liquid mass ratio is controlled to be 1:4; 0.1 parts of sodium dodecylbenzene sulfonate dispersant is added to the ball mill, and ball milling is performed in a sealed state, the ball milling speed is controlled at 200rpm, and the ball milling time is 10h; after the ball milling is completed, the solid material of the ball milling product is separated by centrifugation, and then the solid material is washed 3 times with deionized water; then the washed solid material is dried in a vacuum drying oven at 50°C to constant weight, and finally hexagonal boron nitride is obtained. The average diameter of hexagonal boron nitride is 600nm and the average thickness is 10nm.
[0034] The preparation method of polyphosphazene modified magnesium hydroxide nanowires of the present embodiment is as follows: by weight, 40 parts of magnesium hydroxide nanowires and 200 parts of anhydrous ethanol are stirred at room temperature for 20 minutes, and then 2.0 parts of silane coupling agent KH-550 and 5.0 parts of deionized water are added, and the stirring is continued for 60 minutes. After the stirring is completed, the precipitate is filtered and retained, and then the precipitate is washed with deionized water for 3 times, and finally, the amino-functionalized magnesium hydroxide nanowires are obtained after vacuum drying at room temperature. Then, the amino-functionalized magnesium hydroxide nanowires are dissolved in 180 parts of acetonitrile, and then 8. 0 parts of 4,4'-diaminodiphenyl ether and 20 parts of triethylamine were ultrasonically treated for 25 minutes to obtain a mixed solution of amino-functionalized modified magnesium hydroxide nanowires, and then 50 parts of a mixed solution of hexachlorocyclotriphosphazene and acetonitrile were added dropwise thereto, wherein the mass ratio of hexachlorocyclotriphosphazene to acetonitrile was 1:25. After the addition was completed, the mixture was stirred for 180 minutes at 40 minutes. After the reaction was completed, the solution was filtered and the precipitate was retained and washed with acetonitrile and deionized water for 3 times respectively. Then the washed precipitate was dried in a vacuum drying oven at 40°C to constant weight, and finally polyphosphazene modified magnesium hydroxide nanowires were obtained. The preparation method of magnesium hydroxide nanowires is as follows: 0.4 mol of magnesium nitrate hexahydrate and 5 mol of 50 wt.% sodium hydroxide solution are ultrasonically treated for 20 minutes to obtain a uniform solution, 2 mol of anhydrous ethanol is added and stirred for 5 minutes, and then the solution is added into a Teflon-lined autoclave, heated to 180°C and kept warm for 5 hours, and after cooling to room temperature, the solution is filtered and the precipitate is retained, followed by washing with deionized water for 6 times, and finally dried in a vacuum drying oven at 60°C to constant weight to obtain magnesium hydroxide nanowires.
[0035] The method for preparing the flexible flame-retardant polyolefin insulation material for the highly flexible drag chain cable of this embodiment comprises the following steps: S1. Premixing of raw materials: according to the ratio, add the phosphorus-containing flame retardant surface-modified boron nitride, polyphosphazene-modified magnesium hydroxide nanowires and silane coupling agent KH550 into a high-speed mixer and stir. Control the speed to 1200r / min, stir at high speed for 30 minutes to mix evenly, then continue to add the remaining components, and continue stirring at the same speed for 25 minutes to obtain a premix.
[0036] S2. Melt blending: The premix of S1 was put into a twin-screw extruder for melt blending. The temperatures of the extruder zones were set to: 120°C for zone 1, 160°C for zone 2, 190°C for zone 3, and the die temperature was 200°C. During the blending process, the screw speed was controlled at 200 r / min and the melting time was controlled at 3 min.
[0037] S3. Cooling and granulation: After the molten material extruded in step S2 is extruded through an extruder head, the material is cooled to room temperature and sent to a pelletizer through a conveying device, and cut into uniform particles to obtain a flexible flame-retardant polyolefin insulation material masterbatch.
[0038] S4. Extrusion molding: The masterbatch prepared in step S3 is used for extrusion molding of the insulation layer through a single-screw extruder. The barrel temperature of the extruder is set to: 160°C for zone 1, 180°C for zone 2, 200°C for zone 3, the head temperature is 220°C, and the screw speed is controlled at 50r / min. Finally, a flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables is obtained.
[0039] The material prepared in Example 1 of the present invention was subjected to infrared Fourier spectrum analysis and microscopic morphology characterization, and the results showed that: Figure 1 The characteristic absorption peak of hexagonal boron nitride is located at 1371 cm -1 and 813 cm -1 At , it is attributed to the vibration absorption of BN bond; Figure 2 The infrared spectrum of hexagonal boron nitride modified with phosphorus-containing flame retardant shows the characteristic absorption peaks of POC, PC, Si-O-Si and Si-C, which are located at wavenumber 904 cm -1 、1441 cm -1 、1078 cm -1 、1188 cm -1 and 753 cm -1 It indicates that the surface modification is successful; Figure 3 The SEM morphology further confirmed that the modified hexagonal boron nitride has obvious nanosheet morphology; Figure 4 The infrared spectrum of magnesium hydroxide nanowires shows that 3695 cm -1 The strong absorption peak at 455 cm -1 and 580 cm -1 The absorption peak at 1606 cm -1 The CO-Mg absorption peak at MH proves that CO2 is adsorbed on the surface of MH to form CO-Mg; Figure 5 Revealing the phosphazene-modified magnesium hydroxide nanowires at 950 cm -1 、1440 cm -1 and 3400 cm -1 The absorption bands of PN, CH and NH appear at 1630 cm -1 The Si-O-Mg signal at shows that hexachlorocyclotriphosphazene reacts with 4,4'-diaminodiphenyl ether and the amino group of KH550 in triethylamine and acetonitrile solution to generate NH; Figure 6 The morphology of further shows that the magnesium hydroxide nanowires have obvious nanowire morphology. In summary, infrared spectroscopy and morphology characterization jointly verify the successful preparation and structural characteristics of the various functional modified materials in the present invention.
[0040] Example 2 The flexible flame-retardant polyolefin insulation material for high-flexible drag chain cables comprises the following components by weight: 10 parts of phosphorus-containing flame retardant surface-modified boron nitride, 3.9 parts of polyphosphazene-modified magnesium hydroxide nanowires, 0.5 parts of silane coupling agent KH550, 59 parts of polyolefin matrix resin, 4.5 parts of polyethylene grafted maleic anhydride, 0.2 parts of antioxidant 1010, 0.3 parts of ultraviolet absorber 531, 2.9 parts of epoxidized soybean oil, and 0.2 parts of zinc stearate; The preparation method of the phosphorus-containing flame retardant surface-modified boron nitride of the present embodiment is as follows: by weight, 13 parts of hydroxyl-modified hexagonal boron nitride, 33 parts of methanol, 2.9 parts of 60wt.% sulfuric acid and 26 parts of deionized water are added to a beaker, stirred at 230rpm for 20min at room temperature to obtain a solution A, which is then transferred to a constant pressure dropping funnel, and 11.5 parts of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 5.8 parts of vinyltrimethoxysilane are mixed evenly, placed in a three-mouth round-bottom culture bottle, heated to 73°C, and then the A solution is dripped into the three-mouth round-bottom culture bottle drop by drop, reacted at 73°C for 9h after the addition is completed, cooled to room temperature after the reaction is completed, and then the solution is filtered and the precipitate is retained, and then the precipitate is washed with methanol 3 times, and finally the precipitate is dried in a vacuum drying oven at 66°C for 21h to obtain a phosphorus-containing flame retardant surface-modified boron nitride. The preparation method of hydroxyl-modified hexagonal boron nitride is as follows: by weight, 11.5 parts of hexagonal boron nitride and 165 parts of 5 mol / L sodium hydroxide are mixed evenly and reacted at 83°C for 276 minutes. After the reaction is completed, it is cooled to room temperature, and then the solution is filtered and the precipitate is retained. Then, the precipitate is washed with deionized water for 3 times, and finally the precipitate is dried in a vacuum drying oven at 56°C for 11.5 hours to obtain hydroxyl-modified hexagonal boron nitride. The preparation method of hexagonal boron nitride is as follows: by weight, 23 parts of a mixture of hexagonal boron nitride powder and zirconium oxide ball milling medium are added to a ball mill at a mass ratio of 1:8, deionized water is added as a dispersion medium, and the solid-liquid mass ratio is controlled to be 1:5.8; 0.4 parts of sodium dodecylbenzene sulfonate dispersant is added to the ball mill, and ball milling is performed in a sealed state, the ball milling speed is controlled at 290rpm, and the ball milling time is 21h; after the ball milling is completed, the solid material of the ball milling product is separated by centrifugation, and then the solid material is washed 4 times with deionized water; then the washed solid material is dried in a vacuum drying oven at 59°C to constant weight, and finally hexagonal boron nitride is obtained. The average diameter of hexagonal boron nitride is 1020nm and the average thickness is 14.5nm.
[0041] The preparation method of polyphosphazene modified magnesium hydroxide nanowires of this embodiment is as follows: by weight, 46 parts of magnesium hydroxide nanowires and 215 parts of anhydrous ethanol are stirred at room temperature for 23 minutes, and then 2.6 parts of silane coupling agent KH-550 and 6.5 parts of deionized water are added, and the stirring is continued for 69 minutes. After the stirring is completed, the precipitate is filtered and retained, and then the precipitate is washed with deionized water for 3 times, and finally, the amino-functionalized magnesium hydroxide nanowires are obtained after vacuum drying at room temperature. Then, the amino-functionalized magnesium hydroxide nanowires are dissolved in 186 parts of acetonitrile, and then 9.2 parts of 4,4'-diaminodiphenyl ether and 21.5 parts of triethylamine were ultrasonically treated for 28 minutes to obtain a mixed solution of amino-functionalized modified magnesium hydroxide nanowires, and then 53 parts of a mixed solution of hexachlorocyclotriphosphazene and acetonitrile were added dropwise thereto, wherein the mass ratio of hexachlorocyclotriphosphazene to acetonitrile was 1:25. After the addition was completed, the mixture was stirred for 198 minutes at 41.5 minutes. After the reaction was completed, the solution was filtered and the precipitate was retained and washed with acetonitrile and deionized water for 3 times respectively. Then the washed precipitate was dried in a vacuum drying oven at 43°C to constant weight, and finally polyphosphazene modified magnesium hydroxide nanowires were obtained. The preparation method of magnesium hydroxide nanowires is as follows: 0.46 mol of magnesium nitrate hexahydrate and 5 mol of 50 wt.% sodium hydroxide solution are ultrasonically treated for 23 minutes to obtain a uniform solution, 2 mol of anhydrous ethanol is added and stirred for 5 minutes, and then the solution is added into a Teflon-lined autoclave, heated to 192°C and kept warm for 6.5 hours, and after cooling to room temperature, the solution is filtered and the precipitate is retained, followed by washing with deionized water for 6 times, and finally dried in a vacuum drying oven at 66°C to constant weight to obtain magnesium hydroxide nanowires.
[0042] The method for preparing the flexible flame-retardant polyolefin insulation material for the highly flexible drag chain cable of this embodiment comprises the following steps: S1. Premixing of raw materials: according to the ratio, add the phosphorus-containing flame retardant surface-modified boron nitride, polyphosphazene-modified magnesium hydroxide nanowires and silane coupling agent KH550 into a high-speed mixer and stir, control the speed to 1440r / min, stir at high speed for 35 minutes to mix evenly, then continue to add the remaining components, continue stirring at the same speed for 28 minutes to obtain a premix.
[0043] S2. Melt blending: The premix of S1 was put into a twin-screw extruder for melt blending. The temperatures of the extruder zones were set as follows: zone 1 129°C, zone 2 169°C, zone 3 199°C, and die head temperature 209°C. During the blending process, the screw speed was controlled at 230 r / min and the melting time was controlled at 4.2 min.
[0044] S3. Cooling and granulation: After the molten material extruded in step S2 is extruded through an extruder head, the material is cooled to room temperature and sent to a pelletizer through a conveying device, and cut into uniform particles to obtain a flexible flame-retardant polyolefin insulation material masterbatch.
[0045] S4. Extrusion molding: The masterbatch prepared in step S3 is used for extrusion molding of the insulation layer through a single screw extruder. The barrel temperature of the extruder is set to: 166°C in zone 1, 186°C in zone 2, 206°C in zone 3, the head temperature is 229°C, and the screw speed is controlled at 71r / min. Finally, a flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables is obtained.
[0046] Example 3 The flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables comprises the following components by weight: 14 parts of phosphorus-containing flame retardant surface-modified boron nitride, 4.8 parts of polyphosphazene-modified magnesium hydroxide nanowires, 0.6 parts of silane coupling agent KH550, 68 parts of polyolefin matrix resin, 6.0 parts of polyethylene grafted maleic anhydride, 0.3 parts of antioxidant 1010, 0.4 parts of ultraviolet absorber 531, 3.8 parts of epoxidized soybean oil, and 0.2 parts of zinc stearate; The preparation method of the phosphorus-containing flame retardant surface-modified boron nitride of the present embodiment is as follows: by weight, 16 parts of hydroxyl-modified hexagonal boron nitride, 36 parts of methanol, 3.8 parts of 60wt.% sulfuric acid and 32 parts of deionized water are added to a beaker, stirred at 260rpm for 24min at room temperature to obtain a solution A, which is then transferred to a constant pressure dropping funnel, and 13 parts of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 6.5 parts of vinyltrimethoxysilane are mixed evenly, placed in a three-mouth round-bottom culture bottle, heated to 76°C, and then the A solution is dripped into the three-mouth round-bottom culture bottle drop by drop, reacted at 76°C for 10h after the addition is completed, cooled to room temperature after the reaction is completed, and then the solution is filtered and the precipitate is retained, and then the precipitate is washed with methanol 3 times, and finally the precipitate is dried in a vacuum drying oven at 72°C for 23h to obtain a phosphorus-containing flame retardant surface-modified boron nitride. The preparation method of hydroxyl-modified hexagonal boron nitride is as follows: by weight, 13 parts of hexagonal boron nitride and 180 parts of 5 mol / L sodium hydroxide are mixed evenly and reacted at 86°C for 312 minutes. After the reaction is completed, it is cooled to room temperature, and then the solution is filtered and the precipitate is retained. Then, the precipitate is washed with deionized water for 3 times, and finally the precipitate is dried in a vacuum drying oven at 62°C for 13 hours to obtain hydroxyl-modified hexagonal boron nitride. The preparation method of hexagonal boron nitride is as follows: by weight, 27 parts of a mixture of hexagonal boron nitride powder and zirconium oxide ball milling medium are added to a ball mill at a mass ratio of 1:15, deionized water is added as a dispersion medium, and the solid-liquid mass ratio is controlled to be 1:7.6; 0.6 parts of sodium dodecylbenzene sulfonate dispersant are added to the ball mill, and ball milling is performed in a sealed state, the ball milling speed is controlled at 380rpm, and the ball milling time is 33h; after the ball milling is completed, the solid material of the ball milling product is separated by centrifugation, and then the solid material is washed 4 times with deionized water; then the washed solid material is dried in a vacuum drying oven at 68°C to constant weight, and finally hexagonal boron nitride is obtained. The average diameter of hexagonal boron nitride is 1440nm and the average thickness is 19nm.
[0047] The preparation method of polyphosphazene modified magnesium hydroxide nanowires of this embodiment is as follows: by weight, 52 parts of magnesium hydroxide nanowires and 230 parts of anhydrous ethanol are stirred at room temperature for 26 minutes, and then 3.2 parts of silane coupling agent KH-550 and 8.0 parts of deionized water are added, and the stirring is continued for 78 minutes. After the stirring is completed, the precipitate is retained after filtering, and then the precipitate is washed with deionized water for 3 times, and finally, the amino-functionalized magnesium hydroxide nanowires are obtained after vacuum drying at room temperature. Then, the amino-functionalized magnesium hydroxide nanowires are dissolved in 192 parts of acetonitrile, and then 10 .4 parts of 4,4'-diaminodiphenyl ether and 23 parts of triethylamine were ultrasonically treated for 31 minutes to obtain a mixed solution of amino-functionalized modified magnesium hydroxide nanowires, and then 56 parts of a mixed solution of hexachlorocyclotriphosphazene and acetonitrile were added dropwise thereto, wherein the mass ratio of hexachlorocyclotriphosphazene to acetonitrile was 1:25. After the addition was completed, the mixture was stirred for 216 minutes at 43 minutes. After the reaction was completed, the solution was filtered and the precipitate was retained and washed with acetonitrile and deionized water for 3 times respectively. Then the washed precipitate was dried in a vacuum drying oven at 46°C to constant weight, and finally polyphosphazene modified magnesium hydroxide nanowires were obtained. The preparation method of magnesium hydroxide nanowires is as follows: 0.52 mol of magnesium nitrate hexahydrate and 5 mol of 50 wt.% sodium hydroxide solution are ultrasonically treated for 26 minutes to obtain a uniform solution, 2 mol of anhydrous ethanol is added and stirred for 5 minutes, and then the solution is added into a Teflon-lined autoclave, heated to 204°C and kept warm for 8 hours, and after cooling to room temperature, the solution is filtered and the precipitate is retained, followed by washing with deionized water for 6 times, and finally dried in a vacuum drying oven at 72°C to constant weight to obtain magnesium hydroxide nanowires.
[0048] The method for preparing the flexible flame-retardant polyolefin insulation material for the highly flexible drag chain cable of this embodiment comprises the following steps: S1. Premixing of raw materials: according to the ratio, the surface-modified boron nitride of phosphorus-containing flame retardant, polyphosphazene-modified magnesium hydroxide nanowires and silane coupling agent KH550 are added into a high-speed mixer and stirred. The speed is controlled at 1680 r / min and stirred at high speed for 39 minutes to mix evenly. Then, the remaining components are added and stirred for 31 minutes at the same speed to obtain a premix.
[0049] S2. Melt blending: The premix of S1 was put into a twin-screw extruder for melt blending. The temperatures of the extruder zones were set to: 138°C for zone 1, 178°C for zone 2, 208°C for zone 3, and the die temperature was 218°C. During the blending process, the screw speed was controlled at 260 r / min and the melting time was controlled at 5.4 min.
[0050] S3. Cooling and granulation: After the molten material extruded in step S2 is extruded through an extruder head, the material is cooled to room temperature and sent to a pelletizer through a conveying device, and cut into uniform particles to obtain a flexible flame-retardant polyolefin insulation material masterbatch.
[0051] S4. Extrusion molding: The masterbatch prepared in step S3 is used for extrusion molding of the insulation layer through a single screw extruder. The barrel temperature of the extruder is set to: 172°C for zone 1, 192°C for zone 2, 212°C for zone 3, the head temperature is 238°C, and the screw speed is controlled at 92r / min. Finally, a flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables is obtained.
[0052] Example 4 The flexible flame-retardant polyolefin insulation material for high-flexible drag chain cables comprises the following components by weight: 20 parts of phosphorus-containing flame retardant surface-modified boron nitride, 6.0 parts of polyphosphazene-modified magnesium hydroxide nanowires, 0.8 parts of silane coupling agent KH550, 80 parts of polyolefin matrix resin, 8.0 parts of polyethylene grafted maleic anhydride, 0.5 parts of antioxidant 1010, 0.5 parts of ultraviolet absorber 531, 5.0 parts of epoxidized soybean oil, and 0.3 parts of zinc stearate; The surface-modified boron nitride of the phosphorus-containing flame retardant in this embodiment is hydroxyl-modified hexagonal boron nitride obtained by surface modification with 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and vinyltrimethoxysilane; hydroxyl-modified hexagonal boron nitride is hexagonal boron nitride prepared by an alkaline hydrothermal method; the morphology of hexagonal boron nitride is a nanosheet morphology; polyphosphazene-modified magnesium hydroxide nanowires are firstly modified with an amino function of the magnesium hydroxide nanowires by a silane coupling agent KH-550, and then further cross-linked and polymerized with hexachlorocyclotriphosphazene and 4,4'-diaminodiphenyl ether to obtain polyphosphazene-modified magnesium hydroxide nanowires.
[0053] The preparation method of the phosphorus-containing flame retardant surface-modified boron nitride of the present embodiment is as follows: by weight, 20 parts of hydroxyl-modified hexagonal boron nitride, 40 parts of methanol, 5.0 parts of 60wt.% sulfuric acid and 40 parts of deionized water are added to a beaker, stirred at 300rpm for 30min at room temperature to obtain a solution A, which is then transferred to a constant pressure dropping funnel, and 15.0 parts of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 7.5 parts of vinyltrimethoxysilane are mixed evenly, placed in a three-mouth round-bottom culture bottle, heated to 80°C, and then the A solution is dripped into the three-mouth round-bottom culture bottle drop by drop, reacted at 80°C for 12h after the addition is completed, cooled to room temperature after the reaction is completed, and then the solution is filtered and the precipitate is retained, and then the precipitate is washed with methanol 3 times, and finally the precipitate is dried in a vacuum drying oven at 80°C for 25h to obtain a phosphorus-containing flame retardant surface-modified boron nitride. The preparation method of hydroxyl-modified hexagonal boron nitride is as follows: by weight, 15.0 parts of hexagonal boron nitride and 200 parts of 5 mol / L sodium hydroxide are mixed evenly and reacted at 90°C for 360 minutes. After the reaction is completed, it is cooled to room temperature, and then the solution is filtered and the precipitate is retained. Then, the precipitate is washed with deionized water for 3 times, and finally the precipitate is dried in a vacuum drying oven at 70°C for 15 hours to obtain hydroxyl-modified hexagonal boron nitride. The preparation method of hexagonal boron nitride is as follows: by weight, 30 parts of a mixture of hexagonal boron nitride powder and zirconium oxide ball milling medium are added to a ball mill at a mass ratio of 1:20, deionized water is added as a dispersion medium, and the solid-liquid mass ratio is controlled to be 1:10; 1.0 part of sodium dodecylbenzene sulfonate dispersant is added to the ball mill, and ball milling is performed in a sealed state, the ball milling speed is controlled at 500 rpm, and the ball milling time is 48 hours; after the ball milling is completed, the solid material of the ball milling product is separated by centrifugation, and then the solid material is washed 5 times with deionized water; then the washed solid material is dried in a vacuum drying oven at 80°C to constant weight, and finally hexagonal boron nitride is obtained. The average diameter of hexagonal boron nitride is 2000nm and the average thickness is 25nm.
[0054] The preparation method of polyphosphazene modified magnesium hydroxide nanowires of the present embodiment is as follows: by weight, 60 parts of magnesium hydroxide nanowires and 250 parts of anhydrous ethanol are stirred at room temperature for 30 minutes, and then 4.0 parts of silane coupling agent KH-550 and 10 parts of deionized water are added, and the stirring is continued for 90 minutes. After the stirring is completed, the precipitate is retained after filtering, and then the precipitate is washed with deionized water for 3 times, and finally, the amino-functionalized magnesium hydroxide nanowires are obtained after vacuum drying at room temperature. Then, the amino-functionalized magnesium hydroxide nanowires are dissolved in 200 parts of acetonitrile, and then 12. 0 parts of 4,4'-diaminodiphenyl ether and 25 parts of triethylamine were ultrasonically treated for 35 minutes to obtain a mixed solution of amino-functionalized modified magnesium hydroxide nanowires, and then 60 parts of a mixed solution of hexachlorocyclotriphosphazene and acetonitrile were added dropwise thereto, wherein the mass ratio of hexachlorocyclotriphosphazene to acetonitrile was 1:25. After the addition was completed, the mixture was stirred for 240 minutes at 45 minutes. After the reaction was completed, the solution was filtered and the precipitate was retained and washed with acetonitrile and deionized water for 3 times respectively. Then the washed precipitate was dried in a vacuum drying oven at 50°C to constant weight, and finally polyphosphazene modified magnesium hydroxide nanowires were obtained. The preparation method of magnesium hydroxide nanowires is as follows: 0.6 mol of magnesium nitrate hexahydrate and 5 mol of 50 wt.% sodium hydroxide solution are ultrasonically treated for 30 minutes to obtain a uniform solution, 2 mol of anhydrous ethanol is added and stirred for 5 minutes, and then the solution is added into a Teflon-lined autoclave, heated to 220°C and kept warm for 10 hours, and after cooling to room temperature, the solution is filtered and the precipitate is retained, followed by washing with deionized water for 6 times, and finally dried in a vacuum drying oven at 80°C to constant weight to obtain magnesium hydroxide nanowires.
[0055] The method for preparing the flexible flame-retardant polyolefin insulation material for the highly flexible drag chain cable of this embodiment comprises the following steps: S1. Premixing of raw materials: according to the ratio, add the phosphorus-containing flame retardant surface-modified boron nitride, polyphosphazene-modified magnesium hydroxide nanowires and silane coupling agent KH550 into a high-speed mixer for stirring, control the speed to 2000r / min, stir at high speed for 45min to mix evenly, then continue to add the remaining components, and continue stirring at the same speed for 35min to obtain a premix.
[0056] S2. Melt blending: The premix of S1 was put into a twin-screw extruder for melt blending. The temperatures of the extruder zones were set to: 150°C for zone 1, 190°C for zone 2, 220°C for zone 3, and the die temperature was 230°C. During the blending process, the screw speed was controlled at 300 r / min and the melting time was controlled at 7 min.
[0057] S3. Cooling and granulation: After the molten material extruded in step S2 is extruded through an extruder head, the material is cooled to room temperature and sent to a pelletizer through a conveying device, and cut into uniform particles to obtain a flexible flame-retardant polyolefin insulation material masterbatch.
[0058] S4. Extrusion molding: The masterbatch prepared in step S3 is used for extrusion molding of the insulation layer through a single-screw extruder. The barrel temperature of the extruder is set to: 180°C for zone 1, 200°C for zone 2, 220°C for zone 3, the head temperature is 250°C, and the screw speed is controlled at 120r / min. Finally, a flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables is obtained.
[0059] Comparative Example 1 The method is basically the same as Example 1, except that hexagonal boron nitride powder is used instead of hexagonal boron nitride to prepare the surface-modified boron nitride of the phosphorus-containing flame retardant, so the boron nitride does not form a nano-sheet morphology.
[0060] Comparative Example 2 It is basically the same as Example 1, except that the boron nitride is not surface-modified by a phosphorus-containing flame retardant, but a boron nitride with a nano-sheet morphology is used.
[0061] Comparative Example 3 The method is basically the same as Example 1, except that the magnesium hydroxide nanowires are not modified with polyphosphazene.
[0062] Comparative Example 4 The method is substantially the same as Example 1, except that an equal amount of magnesium hydroxide powder is used instead of the magnesium hydroxide nanowires.
[0063] Performance Testing Mechanical properties test: The tensile strength and elongation at break tests are conducted in accordance with GB / T 2951.12 standard using a tensile testing machine. Under standard specimen size, the sample is subjected to tensile loading, and the maximum tensile strength and elongation at break of the sample are recorded during the test to evaluate the mechanical properties and ductility of the material.
[0064] Flame retardant performance test: The flame retardant performance test is carried out according to the UL94 fire test standard. The sample is placed in the flame to observe its combustion behavior and performance, evaluate the safety and fire resistance of the material under fire conditions, and provide a basis for judging the flame retardant grade.
[0065] Resistivity test: According to GB / T 1410-2006 standard, the reference value of the volume resistivity of the sample is measured at 20°C to evaluate the insulation performance and electrical performance stability of the material.
[0066] The properties of the insulating materials of Examples 1 to 4 and Comparative Examples 1 to 4 are summarized in Table 2.
[0067] Table 2 Performance summary of insulation materials of Examples 1 to 4 and Comparative Examples 1 to 4 As can be seen from Table 2, the main difference between Comparative Example 1 and Example 1 is that the morphology of nano-sheet hexagonal boron nitride is not formed, but ordinary hexagonal boron nitride powder is used. As can be seen from Table 2, the failure to form a nano-sheet morphology will significantly reduce the tensile strength, elongation at break, flame retardancy and resistivity. The reinforcing effect of ordinary hexagonal boron nitride powder is significantly weaker than that of the nano-sheet structure, and its surface activity is low and its interfacial bonding with the matrix is poor, resulting in a decrease in mechanical properties and insulation properties. In addition, since hexagonal boron nitride does not form a nano-sheet structure, its specific surface area is small, and its synergistic effect on the flame retardant system is weak, resulting in a decrease in flame retardancy from V-0 to V-1.
[0068] The main difference between Comparative Example 2 and Example 1 is that the nano-flaky hexagonal boron nitride is not surface-modified with a phosphorus-containing flame retardant. As can be seen from Table 2, although the nano-flaky boron nitride without surface modification maintains a partial reinforcement effect, its tensile strength and elongation at break are still lower than those of Example 1, and its resistivity and flame retardant properties also decrease to varying degrees. This is because the surface chemical inertness of the unmodified nano-flaky boron nitride is relatively strong, and the bonding force with the matrix interface is insufficient, resulting in a decrease in mechanical properties and insulation properties. The decrease in flame retardant properties is because the unmodified boron nitride cannot synergize with the phosphorus-containing flame retardant, which weakens the flame retardant effect of the material.
[0069] The main difference between Comparative Example 3 and Example 1 is that the magnesium hydroxide nanowires are not treated with polyphosphazene modification. As can be seen from Table 2, the unmodified magnesium hydroxide nanowires make the tensile strength, elongation at break, flame retardancy and resistivity of the material lower than those of Example 1. This is because polyphosphazene modification can improve the compatibility and dispersibility of magnesium hydroxide nanowires with the matrix, while giving them higher flame retardant efficiency and insulation properties. The unmodified magnesium hydroxide nanowires have poor interfacial bonding and are prone to form stress concentration points in the matrix, resulting in decreased mechanical properties; at the same time, their flame retardant efficiency is low, and the synergistic flame retardant effect cannot be fully exerted, resulting in a decrease in flame retardancy from V-0 to V-1.
[0070] The main difference between Comparative Example 4 and Example 1 is that magnesium hydroxide powder is used instead of magnesium hydroxide nanowires. As can be seen from Table 2, the use of magnesium hydroxide powder significantly reduces the tensile strength, elongation at break, flame retardancy and resistivity of the material. This is because the magnesium hydroxide in powder form has a small specific surface area, poor dispersibility, weak bonding with the matrix, and cannot provide sufficient reinforcement, resulting in a decrease in mechanical properties. At the same time, due to the large particle size of the powder form, its synergistic flame retardant efficiency is low, and a dense carbonized layer cannot be effectively formed, resulting in a decrease in flame retardancy from V-0 to V-1. In addition, the insufficient dispersibility of the powder will also affect the insulation properties of the material, resulting in a further decrease in resistivity.
[0071] In summary, the present invention significantly improves the comprehensive performance of the insulating material by using hexagonal boron nitride with nano-sheet morphology and surface modification of it with a phosphorus-containing flame retardant, and combining it with polyphosphazene-modified magnesium hydroxide nanowires. The morphological structure of nano-sheet hexagonal boron nitride provides excellent reinforcement effect and flame retardant synergy, and the surface modification treatment further improves its interfacial bonding force with the matrix, thereby greatly improving the mechanical properties, flame retardant properties and resistivity of the material. Polyphosphazene-modified magnesium hydroxide nanowires have good dispersibility and interfacial compatibility, and at the same time enhance the flame retardant efficiency and insulation properties of the material. In contrast, the materials in the comparative example that were not modified or structurally optimized showed obvious performance degradation, especially in mechanical properties, flame retardant properties (from V-0 to V-1) and resistivity. This fully illustrates the importance of each key component and its treatment method in optimizing the performance of insulating materials in the present invention, and provides a high-performance flexible flame-retardant polyolefin insulation material solution for the application of high-flexibility drag chain cables.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. Flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables, characterized in that: The invention comprises the following components in parts by weight: 5-20 parts of surface-modified boron nitride containing phosphorus flame retardant, 3.0-6.0 parts of polyphosphazene-modified magnesium hydroxide nanowires, 0.3-0.8 parts of silane coupling agent KH550, 50-80 parts of polyolefin matrix resin, 3.0-8.0 parts of polyethylene grafted maleic anhydride, 0.1-0.5 parts of antioxidant 1010, 0.2-0.5 parts of ultraviolet absorber 531, 2.0-5.0 parts of epoxidized soybean oil and 0.1-0.3 parts of zinc stearate.
2. The flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables according to claim 1, characterized in that: The phosphorus-containing flame retardant surface-modified boron nitride is obtained by surface-modifying hydroxyl-modified hexagonal boron nitride with 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and vinyltrimethoxysilane; The hydroxyl-modified hexagonal boron nitride is prepared by an alkaline hydrothermal method. The morphology of the hexagonal boron nitride is a nano-sheet morphology; The polyphosphazene-modified magnesium hydroxide nanowires are prepared by first modifying the magnesium hydroxide nanowires with amino functionalities using a silane coupling agent KH-550, and then further cross-linking and polymerizing hexachlorocyclotriphosphazene and 4,4'-diaminodiphenyl ether to obtain the polyphosphazene-modified magnesium hydroxide nanowires.
3. The flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables according to claim 1, characterized in that: The preparation method of the phosphorus-containing flame retardant surface-modified boron nitride is as follows: by weight, 10 to 20 parts of hydroxyl-modified hexagonal boron nitride, 30 to 40 parts of methanol, 2.0 to 5.0 parts of 60 wt.% sulfuric acid and 20 to 40 parts of deionized water are added to a beaker, stirred at 200 to 300 rpm for 15 to 30 minutes at room temperature to obtain a solution A, which is then transferred to a constant pressure dropping funnel, and 10.0 to 15.0 parts of 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are taken. After being evenly mixed with 5.0-7.5 parts of vinyltrimethoxysilane, the mixture was placed in a three-necked round-bottom culture bottle and heated to 70-80°C. Then, solution A was dripped into the three-necked round-bottom culture bottle drop by drop. After the addition was completed, the mixture was reacted at 70-80°C for 8-12 hours. After the reaction was completed, the mixture was cooled to room temperature. Then, the solution was filtered and the precipitate was retained. The precipitate was then washed with methanol for 3 times. Finally, the precipitate was dried in a vacuum drying oven at 60-80°C for 20-25 hours to obtain a phosphorus-containing flame retardant surface-modified boron nitride.
4. The flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables according to claim 3, characterized in that: The preparation method of the hydroxyl-modified hexagonal boron nitride is as follows: by weight, 10.0-15.0 parts of hexagonal boron nitride and 150-200 parts of 5 mol / L sodium hydroxide are mixed evenly, reacted at 80-90° C. for 240-360 minutes, cooled to room temperature after the reaction is completed, and then the solution is filtered and the precipitate is retained, then the precipitate is washed with deionized water for 3 times, and finally the precipitate is dried in a vacuum drying oven at 50-70° C. for 10-15 hours to obtain the hydroxyl-modified hexagonal boron nitride.
5. The flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables according to claim 3, characterized in that: The preparation method of hexagonal boron nitride is as follows: by weight, 20 to 30 parts of a mixture of hexagonal boron nitride powder and zirconium oxide ball milling medium are added to a ball mill according to a mass ratio of 1: (5 to 20), deionized water is added as a dispersion medium, and the solid-liquid mass ratio is controlled to be 1: (4 to 10); 0.1 to 1.0 parts of sodium dodecylbenzene sulfonate dispersant is added to the ball mill, and ball milling is performed in a sealed state, the ball milling speed is controlled at 200 to 500 rpm, and the ball milling time is 10 to 48 hours; after the ball milling is completed, the ball milling product is centrifuged to separate the solid material, and then the solid material is washed with deionized water for 3 to 5 times; then the washed solid material is dried in a vacuum drying oven at 50 to 80° C. to constant weight, and finally the hexagonal boron nitride is obtained.
6. The flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables according to claim 2 or 5, characterized in that: The average diameter of the hexagonal boron nitride is 600-2000 nm, and the average thickness is 10-25 nm.
7. The flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables according to claim 1, characterized in that: The preparation method of the polyphosphazene modified magnesium hydroxide nanowires is as follows: by weight, 40 to 60 parts of magnesium hydroxide nanowires and 200 to 250 parts of anhydrous ethanol are stirred at room temperature for 20 to 30 minutes, and then 2.0 to 4.0 parts of silane coupling agent KH-550 and 5.0 to 10 parts of deionized water are added, and the stirring is continued for 60 to 90 minutes. After the stirring is completed, the precipitate is filtered and retained, and then the precipitate is washed with deionized water for 3 times, and finally, the amino-functionalized magnesium hydroxide nanowires are obtained after vacuum drying at room temperature, and then the amino-functionalized magnesium hydroxide is modified. The nanowires were dissolved in 180-200 parts of acetonitrile, and then 8.0-12.0 parts of 4,4'-diaminodiphenyl ether and 20-25 parts of triethylamine were added and ultrasonically treated for 25-35 minutes to obtain an amino-functionalized magnesium hydroxide nanowire mixed solution. Then, 50-60 parts of a mixed solution of hexachlorocyclotriphosphazene and acetonitrile were added dropwise thereto, wherein the mass ratio of hexachlorocyclotriphosphazene to acetonitrile was 1:
25. After the addition was completed, the reaction was stirred at 40-45 minutes for 180-240 minutes. After the reaction was completed, the solution was filtered and the precipitate was retained and washed with acetonitrile and deionized water for 3 times respectively. Then, the washed precipitate was dried in a vacuum drying oven at 40-50°C to constant weight, and finally polyphosphazene-modified magnesium hydroxide nanowires were obtained.
8. The flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables according to claim 7, characterized in that: The preparation method of the magnesium hydroxide nanowires is as follows: 0.4-0.6 mol of magnesium nitrate hexahydrate and 5 mol of 50 wt.% sodium hydroxide solution are ultrasonically treated for 20-30 minutes to obtain a uniform solution, 2 mol of anhydrous ethanol is added and stirred for 5 minutes, and then the solution is added into a Teflon-lined autoclave, heated to 180-220° C. and kept warm for 5-10 hours, and after cooling to room temperature, the solution is filtered and the precipitate is retained, and then washed with deionized water for 6 times, and finally dried in a vacuum drying oven at 60-80° C. to constant weight to obtain the magnesium hydroxide nanowires.
9. The method for preparing a flexible flame-retardant polyolefin insulation material for a highly flexible drag chain cable according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Premixing of raw materials: according to the ratio, the phosphorus-containing flame retardant surface-modified boron nitride, polyphosphazene-modified magnesium hydroxide nanowires and silane coupling agent KH550 are added into a high-speed mixer and stirred, the speed is controlled at 1200-2000 r / min, and the mixture is stirred at high speed for 30-45 min to be uniformly mixed, and then the remaining components are added, and the mixture is stirred for 25-35 min at the same speed to obtain a premix; S2. Melt blending: The premix of S1 was put into a twin-screw extruder for melt blending. The temperature of each temperature zone of the extruder was set to: 120-150°C for zone 1, 160-190°C for zone 2, 190-220°C for zone 3, and the die temperature was 200-230°C. During the blending process, the screw speed was controlled at 200-300 r / min, and the melting time was controlled at 3-7 min. S3 cooling granulation: The molten material extruded in step S2 is extruded through the extruder head, and the material is cooled to room temperature and fed to a pelletizer via a conveying device, and cut into uniform particles to obtain a flexible flame-retardant polyolefin insulation material masterbatch; S4. Extrusion molding: The masterbatch prepared in step S3 is used for extrusion molding of the insulation layer through a single screw extruder. The barrel temperature of the extruder is set to: 160~180℃ for zone 1, 180~200℃ for zone 2, 200~220℃ for zone 3, the head temperature is 220~250℃, and the screw speed is controlled at 50~120 r / min. Finally, a flexible flame-retardant polyolefin insulation material for highly flexible drag chain cables is obtained.
10. Application of the flexible flame-retardant polyolefin insulation material for high-flexibility drag chain cables as described in any one of claims 1 to 8 in dynamic high-flexibility cables in the fields of industrial automation equipment, robots, machine tool manufacturing, and logistics transportation systems.
Citation Information
Patent Citations
Halogen-free nontoxic superB1-grade flame-retardant polyolefin material at 125 DEG C
CN115322573A
Flexible silane crosslinking polyolefin elastomer insulated core
CN201663007U
Method for purifying and synthesizing hexagonal boron nitride in synthetic cubic boron nitride tailings
CN106829889A
Preparation method of magnesium hydroxide one-dimensional material with controllable size
CN108706611A
Method for preparing boron nitride nanoparticles by ball milling method
CN112456455A
Cited By
Processing technology of cable for high-power energy storage power station easy to dissipate heat
CN120727376A
Processing technology of cable for high-power energy storage power station with easy heat dissipation
CN120727376B
Flame-retardant environment-friendly high-flexibility drag chain cable and preparation process thereof
CN120895303A
Micro flat wire self-adhesive composite insulating layer and forming method
CN121851845A
A self-adhesive composite insulation layer with fine flat wire and its molding method
CN121851845B